O corpo do aluno no cotidiano escolar: sentidos e significados atribuídos por um grupo de professores - Lebkuchen, Marcia de Oliveira Pasetto (2013)
The general purpose of this research is to comprehend how the student s body is meant by the teachers from the public network in São Paulo. To do so, the paper found theoretical basement in the Socio-Historical assumptions in which recommend an analysis and interpretation processes must overcome appearances and in a dialectic way, under the light of information about life history, institutional and social conditions of the subject, broadening the discussion and understanding the phenomena genesis. The main matter directs itself to make the individual, from its social environment, becomes human. The main papers on the area, concerning the project, are the research based on Lev S. Vigotski and his followers, who defend the idea of a continuous interaction between social and historical, which is mutable, and the relation with the biological basis of the human behavior. Starting from the body, elementary organic structure and depending on the social experiences to which the individual is exposed, complex mental functions appear, the so-called higher mental functions. Although there is a series of publications and papers in the Socio-Historical area, there are few researches on Education about the significance of the teacher concerning the student s body. This research tried to fill in the gap, supported by the Socio-Historical approach, broadening the debates about the importance of the body during the learning process. Besides the Socio-Historical assumptions, the project was also based on the Human Movement Science. There are many papers concerning Movement and Corporality, such as the ones presented by Sérgio (1994), Kolyniak (2001), Negrão (2008) and Melani (2006). In spite of this, only Carlini s work (1993) focused on the problem of teacher formation to constitute body conception to students, as proposed here. Thus, the project tried to make an original contribution to the study of constitutive aspects in the professional teacher formation and the educational practice in school, broadening Carlini s proposal (1993) and adding Human Movement studies. The main question proposed by the research were the following: (1) How does the teacher plan the given activities considering the student s body? And some specifics questions are: (2) What is the space available in the school environment to develop body activities? (3) Is the school environment appropriate for the development of Human Movement? It is expected that this paper contributed for Educational Psychology by showing results that indicated that the student s body is not meant effectively and considered an important learning language. The paper still presents and discusses the limitations of the research and possible future studies, besides suggestions of pedagogical approaches of its results